Perbedaan Efektivitas Cat Stretch Exercise dengan Pijat Lumbal terhadap Penurunan Dismenore Primer di SMA Negeri 3 Tuban - Khoirur Rosyita; Nur Maziyah Hurin’in; Miftahul Munir; Tri Yunita FD (PPNI UNIMMAN, 2024)
Primary dysmenorrhea is menstrual pain that is generally experienced by young women which is not accompanied by physical disorders or pathology in the reproductive organs. This condition often interferes with daily activities, including academic performance and psychological well-being. Many non-pharmacological approaches are used to reduce the intensity of dysmenorrhea pain, such as massage and physical exercise. This study aims to compare the effectiveness of the Cat Stretch Exercise and lumbar massage in reducing the pain intensity of primary dysmenorrhea at SMA Negeri 3 Tuban. The research design uses True Experimental with the Pretest-Posttest Control Group Design method. A total of 32 female students who experienced primary dysmenorrhea were selected as samples using a purposive sampling technique, divided into two groups: one group was given Cat Stretch Exercise therapy and the other group was given lumbar massage. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after treatment. The results showed that there was a significant reduction in pain in both groups, but the Cat Stretch Exercise was more effective in reducing pain intensity compared to lumbar massage. The p-value obtained was 0.005, which shows a significant difference between the two groups.